Identification of Children's Personality Using Iterative Dichotomizer 3 (ID3) Algorithm: Identifikasi Kepribadian Anak Menggunakan Algoritma Iterative Dichotomiser 3 (ID3) - Sari, Amelia Lukita; Rosyid, Mochamad Alfan (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine the steps of implementing a system to identify the personality of an early childhood and to determine the effect of an early childhood personality identification system on increasing a child's potential to determine their interests and talents. In developing an expert system, the authors use the development method with steps including data collection, analysis, system design, due diligence, program evaluation and implementation. Based on calculations using the ID3 algorithm using the Weka application and manual calculations, it can be seen whether a personality identification is introverted or extroverted. The design of the data classification process is executed to produce a decision tree. From the research based on the research hypothesis, it can be concluded that from the experiments that have been carried out to predict a child's personality using the interactive dichotomous algorithm (ID3) method, predictions can be made to find out a child's personality.